Complementary and alternative therapies research - Field, Tiffany (American Psychological Association, 2009)
"Psychologists and other health practitioners frequently work with patients whose symptoms only partially respond to traditional therapies. Other patients may have been diagnosed with a medical illness and need help coping with both the illness and its treatment. In these and other cases, therapists may wish to consider interventions from among those collectively known as complementary andalternative therapies. This book describes the most common complementary and alternative therapies that have empirical support from peer-reviewed journals and provides guidance on which therapies have been most useful for which psychological and medical issues. In chapters that cover massage and acupressure, acupuncture, Tai Chi, yoga, exercise, hypnosis, meditation, and other therapies, the author documents the positive emotional, behavioral, physiological, and biochemical effects of these therapies as well as proposed mechanisms of change. Additional information is provided on how complementary and alternative therapies can be used in conjunction with traditional therapies. Although focused primarily on adults, the book offers data and guidance on pediatric populations as well. Clear information on the training and credentials of complementary and alternative therapy practitioners is provided as well as contact information for professional associations, so psychotherapists can have confidence in making referrals to and working with these other practitioners. The information is easily accessible to graduate students and medical students as well as novice and seasoned clinicians and researchers"--Jacket. (PsycINFO Database Record (c) 2009 APA, all rights reserved)